Cytosolic free calcium regulation during contraction of isolated neonatal cardiomyocyte : assessment of contractile activity. - Senthil Kumar Manogaran. (2011)
Although defective calcium (Ca2+) regulation has been marked as the cardinal cause of heart failure and the primary genes involved have been investigated in various research publications, definitive research on the interplay between these genes has been lacking. This study explores the nature of contractility in rat neonatal cardiomyocytes by investigating primary genes (RYR2, SERCA & NCX) involved in the Ca2+ regulation pathways. The objectives of this project, in addition to accessing cardiomyocyte contractility, were to ensure that the procedures employed were consistent and reliable. The results revealed that neonatal cardiomyocytes produced contractile responses of slower activation and relaxation periods compared to those of adult cardiomyocytes, highlighting the possible need for differential treatments for newborns and to adult patients. Furthermore, contractility and Ca2+ transient measurements obtained from our new image processing tool were found to be consistent and reliable. High transfection efficiency of 70-80% was achieved and western runs were optimized to detect target proteins. Since abnormal Ca2+ regulation results in the alterations of the Ca2+ transient and contractility measurements, the data will act as control to compare contractile functionality of experimental cells under various pharmacological, physiological and molecular genetic assays in the future.